The Making of Meaning: A Phenomenological Study on Audiovisual Practices in Music Video Productions in Porto - Kieran Esli Engel (2024)
The fusion of audio and visual elements within music videos (MVs) serves as an influential method for artistic expression and storytelling. This research explores the interactions between the two modalities and their effectiveness in conveying meaning in the context of cinematography, editing techniques, visual aesthetics, and the use of semiotics. While existing research has provided valuable insights into the history and technical aspects of music video production, there is a noticeable gap in understanding the lived experiences of visual artists during the creation process. This study aims to fill that gap by employing a phenomenological approach to uncover the emotions, perceptions, and creative processes of these artists. Therefore, this research focuses on the following questions: How do creative individuals behind the production of music videos select and interpret audiovisual elements? What factors drive their creative decision-making process, and how does their artistic expression relate to the intent to convey messages? How do these artists collaborate with other key contributors throughout the music video production process? In order to address these questions, this study manages in-depth interviews with music video industry professionals in Porto, whom are selected through purposive and snowball sampling. A thematic analysis will be conducted on the interview transcripts through inductive coding and theme identification. Additionally, content analysis of episodes from the Director ID series by Canal180, which showcases multiple renowned MV directors and their thought processes, will be performed. The themes gathered from both methods will be cross-referenced and, ultimately, converge into a conceptual framework. Subsequently, the framework will draw upon existing theories to, possibly, support the outcome and extend the theories. The findings of this study are expected to provide perspectives on the creative processes and collaborative dynamics in music video productions. The resulting conceptual framework will offer an understanding of how visual artists in Porto manage audiovisual elements and semiotics in light of conveying meaning and following their own artistry. Hopefully, the framework will contribute to the academic field of audiovisual media and offer practical implications for industry professionals yet to come.